1996
DOI: 10.1002/ana.410390104
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the use of magnetic resonance techniques in monitoring the treatment of multiple sclerosis

Abstract: Because of the major difficulties in measuring clinical end points in multiple sclerosis (MS) treatment trials, there has been much enthusiasm for using magnetic resonance imaging (MRI) findings as an alternative outcome. To provide international consensus guidelines for the use of MRI in MS clinical trials, a task force of the US National MS Society was convened. The recommendations of the task force are presented in this review. Given the high sensitivity for detecting pathological activity in relapsing-remi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
213
2
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(220 citation statements)
references
References 81 publications
(10 reference statements)
1
213
2
4
Order By: Relevance
“…It is widely recognized that although neural cell swelling can be observed under physiological conditions, for example as a result of neurotransmission or intense neuronal discharge (4,(43)(44)(45), larger changes are encountered during pathological conditions, including aging. It is known also that neuronal dehydration in older adults is a reliable predictor of increasing frailty, progressive deterioration in cognitive function and an overall reduction in quality of life [46][47][48][49]. There are a number of hypotheses on regard of detailed role of agedependent cell dehydration in deterioration in cognitive function of brain.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognized that although neural cell swelling can be observed under physiological conditions, for example as a result of neurotransmission or intense neuronal discharge (4,(43)(44)(45), larger changes are encountered during pathological conditions, including aging. It is known also that neuronal dehydration in older adults is a reliable predictor of increasing frailty, progressive deterioration in cognitive function and an overall reduction in quality of life [46][47][48][49]. There are a number of hypotheses on regard of detailed role of agedependent cell dehydration in deterioration in cognitive function of brain.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Within this spectrum of measures, there are basically two avenues to obtain a measure of disease activity: 1) a marker directly linked (specific) to a particular physiological or pathological process, 2) a differential of disease severity measures, obtained at two or more different timepoints. An example of the first is the occurrence of gadolinium-diethylenetriamine penta-acetic acid (Gd-DTPA) contrast enhancement, capturing active focal blood-brain barrier patency, and an example of the second is rates of change of brain parenchymal fraction.…”
Section: Mri Variablesmentioning
confidence: 99%
“…It has already been well established that conventional MRI represents a useful and accurate tool to detect signs of subclinical disease activity. The occurrence of new active lesions (i.e., gadoliniumenhancing lesions on T1-weighted postcontrast sequences) was five-to tenfold more frequent than a clinical relapse, although with a great variability among individuals [19]. In addition, it has been shown that histopathology findings better correlate with MRI than clinical signs [20].…”
Section: Mri For Monitoring Response To Preventive Treatment In Multimentioning
confidence: 99%